An exact algorithm for scheduling tandem quay crane operations in container terminals. (December 2022) - Kong, Lingrui; Ji, Mingjun; Gao, Zhendi
Abstract: This study investigates the scheduling problem of the tandem quay crane (TQC), which is a new type of loading/unloading device used at container terminals. The TQC can execute either a single-lift or tandem-lift at a time. Considering the changeover time between the above two operational modes of the TQC and the weight limitation for executing a tandem-lift, a novel integer linear programming model is established to minimize the time needed for unloading the containers from the containership, and valid inequalities are introduced to enhance the model. Then, an exact algorithm based on logic-based Benders decomposition is applied to solve the problem. The proposed approach decomposes the problem into a mode-assignment master problem and an operation-sequencing slave problem. Logic-based cuts are proposed to ensure the convergence of the algorithm, and several enhancement measures are developed to accelerate the convergence speed. The computational results indicate that the model is superior to the previous model proposed in the literature, and the proposed inequalities are effective. Moreover, the exact algorithm was verified to be efficient for solving realistically sized instances within an acceptable time. Highlights: The tandem quay crane scheduling problem is addressed in this study. A novel formulation is established by making the use of the bay configuration. An exact algorithm based on the logic-based Benders decomposition is developed. The model is proved to be superior to the previous one in the literature. The exact algorithm is efficient for solving the realistically sized instances.